Southeast Asia : - Harrison, Brian (Macmillan & co., 1963)
This book brings shape to the idea that 'to understand the present and to anticipate the future, one must know enough of the past, enough to have a sense of the history of a people.' With an approachable writing style and comprehensive content, this unique text was written for business readers interested in improving their understanding of this important region.